Oscillometrically Measured Aortic Pulse Wave Velocity Reveals Asymptomatic Carotid Atherosclerosis in a Middle-Aged, Apparently Healthy Population. (18th January 2020) - Böcskei, Renáta Marietta; Benczúr, Béla; Müller, Veronika; Bikov, András; Székely, Andrea; Kahan, Thomas; Lenkey, Zsófia; Husznai, Róbert; Cziráki, Attila; Illyés, Miklós
Abstract : Background . Asymptomatic atherosclerosis is a common entity even at young age. Studies have suggested a strong relationship between increased arterial stiffness and asymptomatic carotid atherosclerosis (ACA) in general population, particularly in those with high cardiovascular risk, but no data exist from a younger population free from recognized cardiovascular disease. Hypothesis . We hypothesized there is an association between ACA and aortic pulse wave velocity (PWVao) in middle-aged, apparently healthy, normotensive population to reveal increased cardiovascular risk. Methods . We examined the relationship between ACA and PWVao in 236 apparently healthy, asymptomatic, normotensive, middle-aged subjects (age 47 ± 8 years; 52% women). PWVao was measured with the oscillometric method (Arteriograph). ACA was assessed by carotid artery ultrasonography. Results . ACA was present in 51 subjects. Subjects with ACA were older (p < 0.009 ), more likely to be smokers (p < 0.001 ), and had higher systolic blood pressure (SBP, 128 ± 9 vs. 125 ± 10 mmHg, p = 0.048 ) and PWVao (9.3 ± 1.6 vs. 7.9 ± 1.3 m/s, p < 0.001 ) than subjects without ACA. In a stepwise logistic regression analysis, only PWVao (odds ratio: 1.88, p < 0.001 ), smoking habit (odds ratio 3.79, p = 0.003 ), systolic blood pressure (odds ratio 1.05, p = 0.046 ), and diastolic blood pressure (odds ratio: 0.94, p = 0.038 ) were independently associated with ACA. PWVao >8.3 m/s identified ACA with a 71% sensitivity, 65% specificity, 36% positive and 89% negative predictive value, 2.04 relative risk, and 4.54 odds ratio, respectively. Conclusions . PWVao measured by the Arteriograph proved to be an independent marker of ACA. Our study may reveal high CV risk, detected as increased PWVao, which according to our study is related in a very high probability to asymptomatic carotid atherosclerosis in apparently healthy, young, and middle-aged subjects.